When should one perform shockwave lithotripsy for lower caliceal stones? - (:unkn) unknown (MARY ANN LIEBERT INC PUBL, 1995)
Extracorporal shockwave lithotripsy of lower caliceal stones is often unrewarding because of the difficulty of passing stone fragments. We report our results in SWL of lower pole stones in 219 patients and compare them with the results of SWL of middle (82 patients) and upper pole (85 patients) stones. The stone-free rate of SWL monotherapy was found to be 59%, 77%, and 64% in lower, middle, and upper caliceal stones, respectively. In lower pole stones, SWL was unsuccessful in 41% of the patients, of whom 9% had minimal residual asymptomatic stones (less than 4 mm in greatest diameter). In comparison with the results of percutaneous nephrolithotomy (PCN) of lower pole urolithiasis in the literature, SWL was unsuccessful in large stones, with stone-free rates of 13% and 0 when the stone size was 3 to 4.9 cm(2) and >5 cm(2), respectively. A stone-free rate of 82% when the stone burden was <1 cm(2) is similar to the PCN results of other centers, suggesting that SWL may be the first choice of treatment in lower pole stones of this size. We achieved a stone-free rate of 59% when the stone size was between 1 and 3 cm(2), which is lower than the stone-free rates of PCN in the literature. In spite of its lower stone-free rates, SWL, with its lower morbidity, may still be considered an acceptable treatment modality in this range of moderate stone burden, especially when there is a patient desire for conservative treatment.
Keywords: WAVE LITHOTRIPSY; EXPERIENCE; MONOTHERAPY; CALCULI